Structural Estimation and Solution of International Trade Models with Heterogeneous Firms - Edward J. Balistreri; Russell H. Hillberry; Thomas F. Rutherford (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
We present an empirical implementation of a general-equilibrium model of international trade with heterogeneous manufacturing firms. The theory underlying our model is consistent with Melitz (2003). A nonlinear structural estimation procedure identifies a set of core parameters and unobserved firm-level trade frictions that best fit the geographic pattern of trade. Once the parameters are identified, we utilize a decomposition technique for computing general-equilibrium counterfactuals. We illustrate this technique using trade and protection data from the Global Trade Analysis Project (GTAP). We first assess the economic effects of reductions in measured tariffs. Taking the simple-average welfare change across regions the Melitz structure indicates welfare gains from liberalization that are nearly four times larger than in a standard policy simulation model. Furthermore, when we compare the economic impact of tariffs with reductions in estimated fixed trade costs we find that policy measures affecting the fixed costs of firmentry are of greater importance than conventional tariff barriers.
Keywords: C68; F12; 330; Allokation; Internationale Wirtschaft; Markteintritt; Branchenentwicklung; Produktivität; Handelsliberalisierung; Theorie